(untitled) (Vietnam Journal of Community Medicine, 2026)
Problem statement: The quality of corporate health check-up services directly affects employees’ experience and the sustainability of cooperation between healthcare facilities and companies. Objectives: (1) To describe the quality of corporate health check-up services at Hong Duc II General Hospital in 2025; (2) to analyze selected factors associated with service quality assessment. Methods: A descriptive cross-sectional study was conducted among 274 corporate employees. The instrument was based on the 22-item SERVPERF scale with five dimensions. Descriptive statistics, Chi-square/Fisher’s exact tests, and univariable logistic regression were used to estimate crude ORs with 95% confidence intervals; p<0.05 was considered statistically significant. Results: The overall service quality score was 4.72 ± 0.47; 92.3% rated service quality as good. Tangibility had the highest score (4.80 ± 0.38; 98.2% good), whereas empathy had the lowest score (4.59 ± 0.60; 89.8% good). Employees who regularly underwent periodic health check-ups were more likely to rate service quality as good (crude OR=8.27; p=0.001), as were those who had used other health facilities (crude OR=3.58; p=0.004). Conclusion: The quality of corporate health check-up services was high; improvement should focus on empathy, especially communication, counselling, and individualized support.